Composing Through the Transformation Technique - Rajasingam Solomon, Caroline Selvarani (1998)
This project paper is an investigation of how language teachers can effectively utilise transformations of stories to motivate students to generate ideas, and write creatively a story of their own using what they have read as a guide or model. Twenty form one volunteers wrote two transformations based on the original story, "The Silkie". The transformations were then compared with the original story in terms of changes made. This study indicates that transformations can be used in Malaysia as a means to motivate ESL students to generate ideas and increase their fluency in writing as students wrote interesting stories of their own using culturally familiar ideas. This study also reveals that students can be trained to write, if fluency and not correctness is emphasised in the writing classroom.